Naringin Alleviates Digoxin-induced Nephrotoxicity via Regulating Nrf2/ HO-1 and PI3K/ AKT/TGF-β Cascades in Rats’ Renal Tissues - Said, Hoda K.; Rabie, Al Shaimaa Ibrahim; Said, Amira S.A.; AlAhmad, Mohammad M.; Hussein, Raghda. R.S.; Mohamed, Mohamed M.; El-Kalaawy, Asmaa M.; Hashem, Khalid S.; Ahmed, Amr E. (Current Pharmaceutical Biotechnology, 2025)
<span class=
Keywords: digoxin